Metabolic Complications among Korean Patients with HIV Infection: The Korea HIV/AIDS Cohort Study - Oh, Dong Hyun; Ahn, Jin Young; Kim, Sang Il; Kim, Min Ja; Woo, Jun Hee; Kim, Woo Joo; Baek, Ji Hyeon; Kim, Shin-Woo; Choi, Bo Youl; Lee, Mi Hwa; Choi, Ju-yeon; Han, Myung Guk; et al. (Journal of Korean medical science, 2017)
Currently, metabolic complications are the most common problem among human immunodeficiency virus (HIV)-infected patients, with a high incidence. However, there have been very few studies regarding metabolic abnormalities published in Asia, especially in Korea. This cross-sectional study was performed to investigate the prevalence of and risk factors for metabolic abnormalities in 1,096 HIV-infected patients of the Korea HIV/AIDS cohort study enrolled from 19 hospitals between 2006 and 2013. Data at entry to cohort were analyzed. As a result, the median age of the 1,096 enrolled subjects was 46 years, and most patients were men (92.8%). The metabolic profiles of the patients were as follows: median weight was 63.8 kg, median body mass index (BMI) was 22.2 kg/m², and 16.4% of the patients had a BMI over 25 kg/m². A total of 5.5% of the patients had abdominal obesity (waist/hip ratio ≥ 1 in men, ≥ 0.85 in women). Increased levels of fasting glucose, total cholesterol, low-density lipoprotein (LDL) cholesterol, and triglycerides were present in 10.4%, 6.0%, 5.5%, and 32.1% of the patients. Decreased high-density lipoprotein (HDL) cholesterol levels were observed in 44.2% of the patients. High systolic blood pressure was present in 14.3% of the patients. In multivariate analysis, high BMI and the use of protease inhibitors (PIs) were risk factors for dyslipidemia in HIV-infected patients. In conclusion, proper diagnosis and management should be offered for the prevalent metabolic complications of Korean HIV-infected patients. Further studies on risk factors for metabolic complications are needed.